Effect of Temperature on the Aging rate of Li Ion Battery Operating above Room Temperature - Leng, Feng (2015)
Temperature is known to have a significant impact on the performance, safety, and cycle lifetime of lithium-ion batteries (LiB). However, the comprehensive effects of temperature on the cyclic aging rate of LiB have yet to be found. We use an electrochemistry-based model (ECBE) here to measure the effects on the aging behavior of cycled LiB operating within the temperature range of 25 °C to 55 °C. The increasing degradation rate of the maximum charge storage of LiB during cycling at elevated temperature is found to relate mainly to the degradations at the electrodes, and that the degradation of LCO cathode is larger than graphite anode at elevated temperature. In particular, the formation and modification of the surface films on the electrodes as well as structural/phase changes of the LCO electrode, as reported in the literatures, are found to be the main contributors to the increasing degradation rate of the maximum charge storage of LiB with temperature for the specific operating temperature range. Larger increases in the Warburg elements and cell impedance are also found with cycling at higher temperature, but they do not seriously affect the state of health (SoH) of LiB as shown in this work.